Das bresilionische Deitsch unn die deitsche Bresilioner: en Hunsrickisch Red fo die Sprocherechte - Altenhofen, Cléo V.; Frey, Jaqueline (Contingentia, 2008)
This paper is a contribution of the area of linguistic policies to the discussion of linguistic rights of speakers of minority languages in Brazil. The text, bilingual in Portuguese and Hunsrückisch, one of the varieties of German immigration languages spoken in Brazil, was presented by the authors (as native speakers and translators), in the Legislative Seminar on Creation of the Book of Language Registers, organized by the Institute of National Artistic Heritage (IPHAN), Institute of Investigation and Development in Linguistic Policies (IPOL) and Education and Culture Committee of the Chamber of Representatives, in Brasília, on March 2006. The idea of the Book of Languages contributes to the recognition of Brazilian linguistic diversity, represented by approximately 210 languages, from which 180 are autochthonous (indigenous) and around 30 are allochthonous (of immigration). Its recognition as an immaterial (virtual) cultural heritage is seem as an important act in favor of speakers’ linguistic rights and against linguistic prejudice that comes along with the use of minority languages in contact with the Portuguese language. This work is inserted in this perspective and it comes along with a supportive bibliography and a map of bilingual areas in the south of Brazil.